An Assessment on Mt. Pico De Loro as a Potential ecotourim destination - Tracy Ann Juico Ablaza, Cristina Ramos Batoon, Melody Rabino Dela Cerna, Jobelle Patani Malimban and Mary Joy De Castro Ruffy. 4 0 16; 5
u
Undergraduate Thesis (B.S. in Travel and Tourism Managemnet) Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2